Desempenho operacional de semeadora em função de mecanismos de corte, velocidade e solos, no sistema plantio direto do milho - Mahl, Denise [UNESP] (2006)
The success of no tillage system is directly related to the selection and efficiency of the seeders components as well as of the suitability of the forward speed and soil and vegetable covering characteristics. This research was carried out in a corn (Zea mays L.) field aiming to evaluate the operational and energetic performance of a no-tillage seeder in two soil types with different vegetable covering and with different forward speeds, furrow opener and cut elements. The performance were evaluated through parameters of seeds longitudinal uniformity distribution, seeding depth, soil mobilized area, tractor and seeder tractive wheel slips, draw bar pull and power requirements, fuel consumption, plantules emergency, culture growing and productivity. The experiments were carried out in two different farms. One at Lageado Experimental Farm, which the soil is classified as Nitossolo Vermelho distroférrico covered with 7 t.ha-1 of dry matter of corn, lupine and weed residues. The other experiment was carried out at São Manuel Experimental Farm, wich soil is classified as Latossolo Vermelho covered with 20 t.ha-1 of dry matter of Brachiaria spp and corn residues. Both experiments designs were 2x3x3 factorial in randomized blocks with four replications. The factors examined were: two furrow opener mechanisms (doubledisk and chisel opener); three tractor-seeder forward speeds (5.5; 7.9 and 10.1 km.h-1); and three covering cut mechanisms (smoothly, fluted and notched cut disks). The soil type and vegetable coverage interfered in the global seeder 4 performance and their cut and furrow opener components. Comparing with the experiment carried in Botucatu, the experiment carried in São Manuel provided larger values of: seeding depth, tractor wheel slip, percentage of soil covering, draw bar pull and power requirements, hourly... (Complete abstract, click electronic access below)